Hubungan Intelegensi Interpersonal dengan Hasil Belajar Biologi - Misahradarsi Dongoran (Bioedunis Journal, 2022)
This study aims to determine the relationship of interpersonal intelligence with biology learning outcomes and to determine the contribution of interpersonal intelligence to biology learning outcomes, the sampling technique was carried out by total sampling, the data collection tool was a closed questionnaire. The results of the analysis of the data obtained are "there is no significant relationship between interpersonal intelligence and biology learning outcomes, based on the calculation of the correlation coefficient, the magnitude of the correlation value (r) (0.12) is between 0.00-0.20, meaning interpersonal intelligence has a very low and even negligible correlation interpretation on biology learning outcomes and the magnitude of the contribution of interpersonal intelligence is only 1.5% on biology learning outcomes.